High contrast race and gender in contemporary Hollywood film - Willis, Sharon 1955- (Duke University Press, 2014)
Pt. 1. Battles of the sexes. Mutilated masculinities and their prosthesis: Die Hards and Lethal Weapons. Insides out: public and private exchanges from Fatal Attraction to Basic Instinct. Combative femininity: Thelma and Louise and Terminator 2 -- Pt. 2. Ethnographies of the "White" gaze. Do the wrong thing: David Lynch's perverse style. Tell th right story: Spike Lee and the politics of representative style. Borrowed "Style": Quentin Tarantino's figures of masculinity